2016
DOI: 10.1186/s40580-016-0077-7
|View full text |Cite
|
Sign up to set email alerts
|

Engineered peptide-based nanobiomaterials for electrochemical cell chip

Abstract: Biomaterials having cell adhesion ability are considered to be integral part of a cell chip. A number of researches have been carried out to search for a suitable material for effective immobilization of cell on substrate. Engineered ECM materials or their components like collagen, Poly-l-Lysine (PLL), Arg-Gly-Asp (RGD) peptide have been extensively used for mammalian cell adhesion and proliferation with the aim of tissue regeneration or cell based sensing application. This review focuses on the various approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Next, we aimed to use CAuNEs as real-time cell-based biosensors that are different from numerous previously reported typical dopamine sensors. Specifically, cells are known to actively interact with their surroundings via binding events between cell adhesion receptors such as integrins and ECM proteins 48 . Interestingly, many studies reported that nanopatterns generated on the underlying substrates affect several aspects of cell behavior and cell functions, including migration, proliferation, adhesion, spreading, and differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we aimed to use CAuNEs as real-time cell-based biosensors that are different from numerous previously reported typical dopamine sensors. Specifically, cells are known to actively interact with their surroundings via binding events between cell adhesion receptors such as integrins and ECM proteins 48 . Interestingly, many studies reported that nanopatterns generated on the underlying substrates affect several aspects of cell behavior and cell functions, including migration, proliferation, adhesion, spreading, and differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, the 3D pGO-GNP-pGO is excellent for dopamine detection and could be utilized for the development of biosensors that are capable of detecting other types of neurotransmitters Sensors 2017, 17, 861 9 of 11 (e.g., glutamate, acetylcholine, serotonin, gamma-Aminobutyric acid), and these might be helpful for the early diagnosis of various neurological diseases [41].…”
Section: Discussionmentioning
confidence: 99%
“…To this end, several adhesion molecules of extracellular matrix (ECM) proteins such as collagen, fibronectin, and their peptide derivatives like poly L-lysine, RGD peptide etc. have been explored [24]. Though collagen and fibronectin offer good adhesion properties and create in vivo like environment on the artificial surface, their inhibitory roles in electron exchange phenomena at cell-electrode interface makes them unsuitable for application on electrode surfaces [25,26].…”
Section: Rgd Functionalization Of Cs-go Filmmentioning
confidence: 99%